Trends in international relations in the study of China (2007)
The growing importance of China in the international system requires research to be done from the field of International Relations. In order for these studies to render accuracy and pertinence it is first necessary to inquire as to which theory and which methodological tools best serve to approach issues in relations to China. In the West prevalence has been given to Political Realism, while recognizing the growing Chinese economy has led others to look into liberal approaches, and there are also a number of studies done on bilateral relations and foreign policy. While these can bring to light certain aspects, they lack greatly in giving a comprehensive understanding of China’s contemporary position and behavior in the international system to the degree that they are Statist and that they cannot readily acknowledge the globalizing forces which highly determine and constrain the State’s actions.